A multicenter photoprovocation study to identify potential biomarkers by global peptide profiling in cutaneous lupus erythematosus. (November 2015) - Calderon, C; Zucht, H-D; Kuhn, A; Wozniacka, A; Szepietowski, J C; Nyberg, F; Weichenthal, M; Piantone, A; Budde, P
Cutaneous lupus erythematosus (CLE) is an inflammatory autoimmune skin disease in which abnormal photosensitivity is an important pathogenetic factor but is difficult to predict, creating a challenge in determining treatment efficacy. Although photosensitivity in CLE patients may change over time, photoprovocation testing with ultraviolet (UV) A and UVB irradiation can be a helpful tool to explore differences between responders and nonresponders during photoprovocation. To identify biomarkers that could substitute for the clinical endpoint lesion development, we performed a global peptidomics profiling analysis of CLE subjects in a controlled photoprovocation study. Plasma and skin biopsy samples were collected before and after UV-irradiation from 13 healthy volunteers and 47 CLE subjects. Twenty-two of the 47 CLE subjects developed skin lesions. The samples were analyzed using a label-free quantitative peptidomics workflow combined with univariate and multivariate statistical analyses. The primary finding was identification of a specific plasma peptide signature separating responders versus nonresponders at baseline. The peptide signature consisted of beta 2-microglobulin (B2MG), human beta-defensin-1, and peptides derived from CD99, polymeric immunoglobulin receptor, and immunoglobulin kappa light chains. In skin, elevated B2MG levels correlated with lesion formation. Our results show that the peptidome is a rich source of potential biomarkers for predicting photosensitivity in CLE.